Label-free mass spectrometric analysis reveals complex changes in the brain proteome from the mdx-4cv mouse model of Duchenne muscular dystrophy. Issue 1 (December 2015) - Murphy, Sandra; Zweyer, Margit; Henry, Michael; Meleady, Paula; Mundegar, Rustam; Swandulla, Dieter; Ohlendieck, Kay
Abstract Background X-linked muscular dystrophy is a primary disease of the neuromuscular system. Primary abnormalities in theDmd gene result in the absence of the full-length isoform of the membrane cytoskeletal protein dystrophin. Besides progressive skeletal muscle wasting and cardio-respiratory complications, developmental cognitive deficits and behavioural abnormalities are clinical features of Duchenne muscular dystrophy. In order to better understand the mechanisms that underlie impaired brain functions in Duchenne patients, we have carried out a proteomic analysis of total brain extracts from themdx -4cv mouse model of dystrophinopathy. Results The comparative proteomic profiling of themdx -4cv brain revealed a significant increase in 39 proteins and a decrease in 7 proteins. Interesting brain tissue-associated proteins with an increased concentration in themdx -4cv animal model were represented by the glial fibrillary acidic protein GFAP, the neuronal Ca2+ -binding protein calretinin, annexin AnxA5, vimentin, the neuron-specific enzyme ubiquitin carboxyl-terminal hydrolase isozyme L1, the dendritic spine protein drebrin, the cytomatrix protein bassoon of the nerve terminal active zone, and the synapse-associated protein SAP97. Decreased proteins were identified as the nervous system-specific proteins syntaxin-1B and syntaxin-binding protein 1, as well as the plasma membrane Ca2+ -transporting ATPase PMCA2 that is mostly found in the brain cortex. The differential expression patterns of GFAP, vimentin, PMCA2 and AnxA5 were confirmed by immunoblotting. Increased GFAP levels were also verified by immunofluorescence microscopy. Conclusions The large number of mass spectrometrically identified proteins with an altered abundance suggests complex changes in themdx -4cv brain proteome. Increased levels of the glial fibrillary acidic protein, an intermediate filament component that is uniquely associated with astrocytes in the central nervous system, imply neurodegeneration-associated astrogliosis. The up-regulation of annexin and vimentin probably represent compensatory mechanisms involved in membrane repair and cytoskeletal stabilization in the absence of brain dystrophin. Differential alterations in the Ca2+ -binding protein calretinin and the Ca2+ -pumping protein PMCA2 suggest altered Ca2+ -handling mechanisms in the Dp427-deficient brain. In addition, the proteomic findings demonstrated metabolic adaptations and functional changes in the central nervous system from the dystrophic phenotype. Candidate proteins can now be evaluated for their suitability as proteomic biomarkers and their potential in predictive, diagnostic, prognostic and/or therapy-monitoring approaches to treat brain abnormalities in dystrophinopathies.